THE ROLE OF SPIRITUAL MINDFULNESS THERAPY IN INCREASING SELF-ACCEPTANCE AMONG ADOLESCENT - Muhamad Jauhar; Ashri Maulida Rahmawati; Anny Rosiana Masithoh; Edita Pusparatri ((IJP) Indonesia Jurnal Perawat, 2025)
Evaluation of the benefits of spiritual therapies, such as mindfulness, for adolescent mental health is needed. Adolescence is a difficult period for self-adjustment and is particularly vulnerable to decreased self-acceptance. In today's educational environment, adolescents often experience various crises that are largely due to low self-acceptance. Spiritual mindfulness is a strategy that is easy to implement and can help adolescents recognize problems without judgment, thus reducing the cost and time required in the therapeutic process. This study aims to determine the effect of spiritual mindfulness on increasing self-acceptance in adolescents. The research design used was a pre-experiment with pre-test and post-test methods and involved a control group. Through purposive sampling, twenty-six high school students in Kudus were selected as respondents and divided into intervention and control groups. The study used the Unconditional Self-Acceptance Questionnaire (USAQ). The researcher conducted six sessions of mindfulness therapy, each lasting 30 minutes for two days. The results showed a statistically significant difference in self-acceptance in the intervention group before and after the intervention, with a value of p=0.04 (p0.05). In contrast, in the control group, no significant difference was found with a value of p=0.477 (p0.05). The intervention group showed an increase in self-acceptance of 1.46 higher than the control group. However, the overall effect of mindfulness therapy was less significant in improving self-acceptance in adolescents p=0.332 (p0.05). Changes need to be made in the way spiritual mindfulness therapy is delivered to adolescents to see a more noticeable improvement in self-acceptance.